Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Kompetensi Digital Citizenship Siswa pada Mata Pelajaran Pendidikan Pancasila: Implementation of the Project-Based Learning Model to Enhance Students' Digital Citizenship Competence in the Pancasila Education Subject - Ely Solihin; Iim Siti Masyitoh; Syaifullah Syaifullah (ITScience (Information Technology and Science), 2026)
The digital era requires students to possess Digital Citizenship competencies to use technology wisely, ethically, and responsibly. However, many students still fail to utilize technology productively and ethically. Therefore, this study aims to analyze the implementation of the Project-Based Learning (PjBL) model in Pancasila Education to enhance students' Digital Citizenship competencies at SMA YAS Bandung. The study employs a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consists of two classes—an experimental class receiving the PjBL treatment and a control class undergoing conventional instruction—with 34 students in each. Data collection involved pre-tests and post-tests, while data analysis utilized normality tests, homogeneity tests, paired t-tests, independent t-tests, and normalized gain (N-Gain) calculations. The results indicate a significant improvement in Digital Citizenship competencies in both groups, with the experimental class showing a greater increase. The experimental class's average score rose with an N-Gain of 0.61 (medium-to-high category), whereas the control class achieved only 0.24 (low category). The independent t-test yielded a significance value of < 0.05, confirming a significant difference between the two groups. The implementation of the Project-Based Learning (PjBL) model proved effective in enhancing students' digital literacy, digital ethics, and digital security, as well as their participation and responsibility within the digital space. Furthermore, this model fosters a more active, collaborative, and contextual learning experience, making it highly relevant for Pancasila Education in the digital era.